Influence Of Integrity, Career Development And The Provision Of Additional Employee Income On The Work Productivity Of Employees In The Regional Secretariat Of Pasaman Regency - padri son; Syamsir Syamsir (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
Background – Work productivity is a real result (product) created by individuals or groups. In this situation, the more products produced in less time, the more valuable the productivity level. Work productivity in the organization is one of the goals that must be achieved by every organization. Thus the low productivity of employees will affect the goals of the organization. In the study the low work productivity of employees at the Regional Secretariat of Pasaman Regency. Purpose – The aims of this research are analyze the effect of integrity, career development and the provision of additional employee income on the work productivity of employees at the Pasaman Regency Secretariat. Work productivity is often used by private organizations with the aim of measuring inputs and outputs within the organization. But in this article work productivity is measured in government agencies. Design/ Methodology/ Approach - This research was conducted at the Regional Secretariat of Pasaman Regency. The sampling technique used in this study is total sampling. The total population in this study amounted to 117 respondents. Analysis of research data using multiple linear regression analysis with the help of the IBM SPSS Statistics 26 program as statistical data processing. Finding – The results showed that (1) There is an influence of integrity on the work productivity of employees in the Regional Secretariat of Pasaman Regency (2) There is an effect of career development on the work productivity of employees in the Regional Secretariat of Pasaman Regency. (3) There is an effect of providing additional employee income (TPP) on the work productivity of employees in the Regional Secretariat of Pasaman Regency. (4) There is an influence of integrity, career development and the provision of additional employee income (TPP) on the work productivity of employees in the Regional Secretariat of Pasaman Regency. Conclusion - The leadership of the Pasaman Regency Regional Secretariat must be able to provide encouragement through integrity and career development and be able to provide additional employee income based on the quantity and quality of employee work. Thus the work productivity of employees will be achieved in accordance with the objectives set by the agency. Research Implication – To get good employee integrity at the Regional Secretariat of Pasaman Regency, it is necessary to improve and foster the integrity of good employees. Furthermore, the greater and better career development given at the Regional Secretariat of Pasaman Regency, the greater the work productivity of employees. As well as means that the bigger and better the additional employee income provided, the greater the employee's work productivity. Limitations – The scope of this research is limited to one particular agency, so it cannot reflect the situation of other institutions in the same area regarding integrity, career development and additional employee income.